Automated surgical screwdriver: automated screw placement - R.L. Thomas; Kaddour Bouazza-Marouf; G.J.S. Taylor (2008)
The use of power screwdrivers and drills for tapping and screw insertion in surgery is becoming more common. It has been established from clinical observations that the use of a small air drill for inserting self-tapping screws provides improved coaxial alignment and precision, and that the drill should be stopped before the screw head is completely seated on the plate, presumably to reduce the risk of over-tightening. The risk of overrun and over-tightening during tapping and screw insertion is increased with the use of power tools. Prevention of over-tightening is dependent upon when the surgeon detects the onset of tightening, both visually and from the feel of the rapid increase in torque. If detection is too late, then over-tightening or stripping can occur. This study is concerned with using a mechatronic screwdriver to control the tapping depth and to prevent the over-tightening of screws. The effects of various parameters upon the torque profile during tapping and screw insertion have been investigated in synthetic bone and sheep tibia. An automated system is proposed for preventing over-tightening of pre-tapped and self-tapping screws when attaching a surgical plate to a sheep tibia in vitro. The system was used to attach a plate to a sheep tibia using self-tapping screws. The mean torque of the screws inserted using the automated system was 35 per cent of the stripping torque.